Zonal adjusted PSA density improves prostate cancer detection rates compared with PSA in Taiwanese males with PSA < 20 ng/ml - Chang, Tsung-Hsin (BMC Urol, 2020)
BACKGROUND: The current study aimed to compare the efficacy of transition zone PSA density (TZPSAD) with traditional PSA and PSA density (PSAD), for the diagnosis of prostate cancer (PCa) in Taiwanese males. METHODS: Men with PSA between 4.0 and 20.0 ng/ml who underwent a transrectal ultrasound (TRUS) guided prostate biopsy between the studied period were retrospectively identified. The demographic data, PSAD and TZPSAD were calculated in all patients. Receiver operating characteristic (ROC) curves were used to analyze the accuracy of a positive PCa diagnosis. RESULTS: The area under the ROC (AUC) was 0.615, 0.748 and 0.746 for PSA, PSAD and TZPSAD, respectively. The best cut-off of value for TZPSAD in predicting PCa in men with a PSA of 4.0–10.0 ng/ml was 0.367 ng/ml/ml with a sensitivity of 50% and a specificity of 77.5%. In men with a PSA of 10.1–20.0 ng/ml, the best cut-off value was 0.454 ng/ml, with a sensitivity of 74.8% and specificity of 70.9%. CONCLUSION: The use of TZPSAD can improve the efficiency and specificity of PSA for the diagnosis of PCa in Taiwanese men with PSA 4.0–20.0 ng/ml. TZPSAD efficiency was similar to PSAD but TZPSAD had better cancer specificity.